The Improvement of Labor Activity Motivation of Workers in the Process of Their Socialization in the Organization: The Influence of Organizational Culture - Glaz, Viktor Nikolaevich; Glaz, Yuliya Aleksandrovna; Rusetskaya, Elvira Antsasovna; Zhuravleva, Natalia Vasilevna (Journal of History Culture and Art Research, 2017)
The article considers organizational culture as the basis for a system of managing motivation of workers’ labor activity. It is the control of labor motivation of workers taking into account the features of organizational culture that enables to successfully solve the task of multidimensional and diversified disclosure of human potential in the organization. The authors developed recommendations for improving the motivation of workers’ labor activity in the process of their socialization in the organization that contribute to activation of labor behavior of personnel. In the course of the research the set of basic principles of collective motivation of labor activity of workers formed under the influence of established organizational culture was determined. Possible mechanisms for motivating the labor activity of workers are suggested that is hierarchical, clan, market, adhocratic in accordance with the type of organizational culture. The study specifies the directions of socialization of workers in the organization that are determined by the influence of organizational culture on the development of labor motivation. Alternative models of arranging interaction between workers for the purpose of their socialization in work collective of the organization are presented, considering such types of interaction as competition and cooperation. Practical use of the recommended mechanisms for motivating labor activity will enable organizations to develop effective systems for workers’ stimulation, to optimize the process of their socialization taking into account the peculiarities of organizational culture.